2013
DOI: 10.1099/jmm.0.051854-0
|View full text |Cite
|
Sign up to set email alerts
|

Nasal self-swabbing for estimating the prevalence of Staphylococcus aureus in the community

Abstract: Staphylococcus aureus remains a significant cause of morbidity and mortality and, therefore, a burden on healthcare systems. Our aim was to estimate the current rate of nasal S. aureus carriage in the general population and to determine the feasibility of nasal self-swabbing as a means of detection. Two thousand people (1200 adults and 800 children) from a single NHS general practice in Southampton, UK, were randomly selected from a general practice age sex register, stratified by age and sex, and invited to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
38
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 13 publications
13
38
1
1
Order By: Relevance
“…Every fifth participant of our study was colonized with S. aureus. In Europe, two studies from the UK have shown similar results to our study [17,18]. Gamblin et al [17] found 28% nasal S. aureus colonization in Southampton, which is close to the previous estimate of 23% by Abudu et al [18] in Birmingham.…”
Section: Discussionsupporting
confidence: 91%
“…Every fifth participant of our study was colonized with S. aureus. In Europe, two studies from the UK have shown similar results to our study [17,18]. Gamblin et al [17] found 28% nasal S. aureus colonization in Southampton, which is close to the previous estimate of 23% by Abudu et al [18] in Birmingham.…”
Section: Discussionsupporting
confidence: 91%
“…We fully agree that infection prevention is a priority in any OF because children and adolescents are still developing their immune systems, often have asymptomatic infections (due to MRSA, S. pneumonia, S. pyogenes, H. influenza, Moraxella catarrhalis, HBV, HIV etc), may be at high risk of developing infections (immunocompromised subjects and those predisposed to developing infective endocarditis), or be medically compromised (12)(13)(14)(15)(16)(17)(18)(19). This accounts for the increasing discussion of the medical-legal liability of orthodontists, and underlines the need for established scientific proof concerning prophylactic antibiotic treatment and the prevention of the over-use of antibiotics (19,20) when treating high-risk patients.…”
Section: Orthodontic Patient Safetymentioning
confidence: 99%
“…A thorough review of 18 studies from 1944 until 1994 showed that the mean S. aureus carriage rate in the general population was 37 % (Kluytmans et al 1997). More recent studies have shown nasal colonization rates of 20 % to 30 % (Andersen et al 2012;Gamblin et al 2013;Mernelius et al 2013b;Olsen et al 2013;Mehraj et al 2014). Nasal colonization rates of up to nearly 60 % have been reported among HIV-positive patients (Kotpal et al 2014), patients on hemodialysis (Duran et al 2006), intravenous drug addicts and patients with insulin dependent diabetes (Kluytmans et al 1997).…”
Section: Carriage and Colonizationmentioning
confidence: 99%